Bridging the Gap Between Policy and Science in Assessing the Health Status of Marine Ecosystems, 2nd Edition - Maria C. Uyarra (Frontiers Research Topics, 2017)
Marine management requires approaches which bring together the best research from the natural and social sciences. It requires stakeholders to be well-informed by science and to work across administrative and geographical boundaries, a feature especially important in the inter-connected marine environment. Marine management must ensure that the natural structure and functioning of ecosystems is maintained to provide ecosystem services. Once those marine ecosystem services have been created, they deliver societal goods as long as society inputs its skills, time, money and energy to gather those benefits. However, if societal goods and benefits are to be limitless, society requires appropriate administrative, legal and management mechanisms to ensure that the use of such benefits do not impact on environmental quality, but instead support its sustainable use.